Die alt- und reichsaramäischen Inschriften: Band 1: Konkordanz = The old and imperial aramaic inscriptions - Schwiderski, Dirk (Fontes et subsidia ad Bibliam pertinentes, 2008)
Main description: This collected edition presents the texts of the more than 2500 Old and Imperial Aramaic inscriptions (10th-3rd cents. BC) hitherto published; they cover an area extending from Asia Minor, Egypt, Syria and Palestine to Afghanistan. It serves as a reference volume for the concordance, which provides rapid access to the overall context of every reference. Each text is provided with the most important editions and further bibliographical references. The work thus provides scholars with the total corpus of Old and Imperial Aramaic epigraphs.